Komparasi Paradigma Pendidikan Barat dan Pendidikan Islam: Ontologi, Epistemologi, dan Aksiologi dalams Perspektif Integrasi Ilmu - Mila, Cici; Istiqamah, Istiqamah; Kurniaty, Nela; Faisal, Muhammad (Wahana Islamika Jurnal Studi Keislaman, 2026)
This study starts from the fact that Western educational paradigms range from pragmatic and positivistic tendencies to critical pedagogy, while Islamic education emphasizes education as the cultivation of adab (ta’dib) and responds to secularism through Islamization of knowledge and integration–interconnection models. The study aims to compare both paradigms through ontology, epistemology, and axiology, and to formulate “knowledge integration” as a coherent linkage among educational goals, methods, and evaluation. Using a qualitative library-research design and a comparative–philosophical approach, the analysis applies qualitative content analysis and layered comparison to map OEA propositions and their interrelations. The findings indicate ontological divergence regarding the scope of reality (empirical vs tawhid-based holism), epistemological divergence in sources and validity of knowledge (empirical–rational verification vs ta’dib, Islamization, and bayani–burhani–irfani), and axiological divergence in value orientation (functionality/emancipation vs the formation of an ethical, civilized person). The proposed integration is not mere content combination, but a paradigm reconstruction where values guide knowledge selection and justification.